2019
DOI: 10.32598/rmm.7.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-rich Plasma and Mesenchymal Stem Cells as Two Biological Alternatives in Rotator Cuff Injury Treatment: A Mini-review

Abstract: The rotator cuff injury introduces as significant damage of trauma and others factors, and currently recognized as a prevalent orthopedic problem. Thus, many clinical procedures have been demonstrated to reduce the complication of rotator cuff injury with varying degrees of success. Platelet-Rich Plasma (PRP) is being enchantingly agreed as one of the most effectiveness strategies for the symptomatic treatment of rotator cuff injury. Many confusing parameters can influence the result of PRP including size of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“… 29 , 33 , 36 While multiple animal studies have demonstrated BMAC’s ability to augment tendon repair by improving enthesis regeneration and repair quality, high-level human clinical studies are scarce. 29 , 38 Despite being scarce, the available clinical investigations have shown promise. 38 In one of the first clinical studies, Hernigou et al 15 investigated 90 matched patients who received a single-row RCR for small tears, half of whom received BMAC at the completion of the repair and the other half who did not.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 29 , 33 , 36 While multiple animal studies have demonstrated BMAC’s ability to augment tendon repair by improving enthesis regeneration and repair quality, high-level human clinical studies are scarce. 29 , 38 Despite being scarce, the available clinical investigations have shown promise. 38 In one of the first clinical studies, Hernigou et al 15 investigated 90 matched patients who received a single-row RCR for small tears, half of whom received BMAC at the completion of the repair and the other half who did not.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 38 Despite being scarce, the available clinical investigations have shown promise. 38 In one of the first clinical studies, Hernigou et al 15 investigated 90 matched patients who received a single-row RCR for small tears, half of whom received BMAC at the completion of the repair and the other half who did not. At 6 months, all 45 patients who received BMAC had evidence of healed repairs on MRI compared with only 67% of patients who did not receive BMAC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations